Effective Implementation of Lean Manufacturing in PT Kalbe Farma Tbk - Sulanjari, Prasti; Firman, Aries F (The Indonesian Journal of Business Administration, 2012)
Production costs are influenced by the high average value of inventory. Inventory which meant here are the inventory of materials, semi-finished materials inventory and finished product inventory. To cope with the amount of inventory that is high enough, PT Kalbe Farma Tbk implement lean manufacturing in order to obtain the production process that uses the minimum inventory. The purpose of this study was to determine the effectiveness of the implementation of lean manufacturing in PT Kalbe Farma Tbk and its impact. The study uses secondary data methodology which are lead time, the amount of work in process (WIP) and achievement rate. For three times the period of the determination of lead time and the amount of WIP, obtained trend that the lower lead time and WIP, the lower the amount of achievement rate. One cause that is dominant is the absence of a tablet and after visible roots of the problem is caused by unplanned breakdown. Appropriate to principles of Toyota Production System and Operational Excellence, the basis of the application of lean manufacturing is a system of production, including production machinery, need to be stable. According to Liker, when enginee often stops, management needs to think to implement Total Productive Maintenance (TPM). TPM involves all employees of all levels to maintain engine performance. Keywords : Lean Manufacturing, Lead Time, WIP, Achievement Rate, Total Productive Maintenance